EVALUASI MODEL KIRKPATRICK DIKLAT TEKNIS SUBSTANTIF MODERASI BERAGAMA ANGKATAN I TAHUN 2019 DI BALAI DIKLAT KEAGAMAAN BANJARMASIN - Yasir Arafat (Balai Diklat Keagamaan Banjarmasin, 2021)
To find out whether the training was effective or not, an evaluation was needed. Evaluation is an inseparable part of training activities. An evaluation of the impact of the effectiveness of a training is needed so that the advantages and disadvantages in the program can be identified so that improvements can be followed up. Efforts to improve the quality of training can be pursued through improving the quality of learning and the quality of the evaluation model, this shows the link between the two aspects. Various evaluation models have been developed by evaluation experts and are very popular which can be used as work guidelines for evaluating training program programs. Among the evaluation models include: 1) Kirkpatrick Model Evaluation (Kirkpatrick Four Level Evaluation Models), 2) Evaluation of the CIPP Model (Contest, Input, Process, and Product) and 3) Evaluation of the Stake Model (Couintenance Model). From the three sample models above, each has advantages and disadvantages. The Kirkpatrick evaluation model, is an evaluation model that is widely accepted and used, on the grounds; simple, complete, clear and easy to implement. The evaluation includes four evaluation levels, namely level 1 reaction, level 2 learning, level 3 behavior, and level 4 result. Research only uses two levels in this study, namely levels 3 and 4. Based on the distribution of data conducted on the alumni of Education and Training and the perception of people around the alumni shows that the Technical Training for Substantive Religious Moderation of Class I is in the category of GOOD, VERY GOOD, VERY GOOD or at numbers 81.54-96.67 and 90.00. This acquisition is based on 3 aspects or perceptions, namely; alumni superiors, alumni colleagues, and widyaiswara who support the religious moderation core. Therefore, the Substantive Technical Training of Religion Moderation Class I has a positive impact on the performance of alumni and can contribute positively to their institutions.